Hubungan Sikap, Tingkat Pendidikan, Dan Usia Terhadap Upaya Pencegahan Demam Berdarah di Desa Tanjung Baru - Meyrinda, Lilis; Candra, Elwan; Zanzibar, Zanzibar (JURNAL WACANA KESEHATAN, 2025)
Dengue Hemorrhagic Fever (DHF) is a growing public health issue, particularly in tropical regions like Indonesia. This study aims to examine the relationship between attitudes, education levels, and age with dengue fever prevention efforts in Tanjung Baru Village, Ogan Komering Ulu (OKU) Regency, South Sumatra. A cross-sectional design with a quantitative correlational approach was employed. The sample consisted of 243 respondents selected using accidental sampling. Data were collected through questionnaires and analyzed using the chi-square test with a significance level of 0.05. The results showed a significant relationship between attitudes and dengue prevention efforts (p = 0.004), education levels and dengue prevention efforts (p = 0.010), and age and dengue prevention efforts (p = 0.000). Respondents with positive attitudes, higher education levels, and younger ages were more active in carrying out prevention measures. These findings suggest that attitudes, education, and age play crucial roles in the success of dengue fever prevention. Therefore, it is recommended that health education programs and prevention campaigns be enhanced, especially for groups with low education levels and older age. Increasing community participation in prevention efforts is expected to reduce the incidence of dengue fever in the future.